2020
DOI: 10.4081/or.2020.8668
|View full text |Cite
|
Sign up to set email alerts
|

Wide awake surgery for flexor tendon primary repair: A literature review

Abstract: Flexor tendon injuries are extremely challenging conditions to manage for hand surgeons. Over the last few years enormous progress has been made for the treatment of these lesions with new surgical approaches being performed. One of these is the wideawake local anesthesia no tourniquet (WALANT) technique, also known as Wide Awake Technique that allows tendon repair under local anesthesia, enabling the tendon to move actively during surgery. Dynamic movement of the tendon during surgery is crucial for the ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
11
1
1
Order By: Relevance
“…An open reduction and internal fixation surgery of ankle fractures using WALANT technique reported a mean operation time of 59.72 ± 7.19 min (8), which is approximately the same as the duration recorded in this current study (65.28 ± 39.02 min). Another similar study involving ankle operation reported a shorter mean surgery duration of 36.6 ± 7 min (7).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…An open reduction and internal fixation surgery of ankle fractures using WALANT technique reported a mean operation time of 59.72 ± 7.19 min (8), which is approximately the same as the duration recorded in this current study (65.28 ± 39.02 min). Another similar study involving ankle operation reported a shorter mean surgery duration of 36.6 ± 7 min (7).…”
Section: Discussionsupporting
confidence: 80%
“…The mean EBL recorded in the current study was 91.34 ± 78.94 cc, which is higher compared to the average amount of blood loss recorded (29.40 ± 7.38 ml) in an ankle fracture fixation surgery using the same WALANT technique (8). This is probably due to the majority of patients (50.6%) in this study underwent soft tissue surgery, which may lead to more blood loss compared to procedures involving ankle fracture fixation.…”
Section: Discussioncontrasting
confidence: 69%
“…This can minimise adhesions postoperatively and maximise patient outcomes. [9][10][11] The outcomes of flexor tendon repair using WALANT and traditional anaesthesia showed similar functional outcomes and complications in two recent studies. 19 20 However, WALANT clearly offers the advantage of local anaesthetic combined with the ability to test the repair intraoperatively.…”
Section: Discussionmentioning
confidence: 78%
“…Flexor tendon lacerations are uncommon injuries but remain to be one of the most challenging injuries to treat, especially zone II injuries (figure 1). 8 9 In established flexor tendon lacerations, surgical repair is usually warranted with the traditional manner of using a tourniquet and the patient either sedated under regional or general anaesthesia. In such cases, active movement of the repaired tendon is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not use telemedicine, and Toia et al [11] as well as Leti Acciaro et al [27] confirmed it might be an issue in Italy. To reduce contamination risks [28], some surgeons increased non-surgical treatment [9,23], and to resolve issues linked to a diminution of anesthetists' availability, many hand surgeons [9,12,14,17,24,29] stated to use WALANT surgery [30].…”
Section: Discussionmentioning
confidence: 99%